The Role The Role of Job Satisfaction in Minimizing Turnover Intention in Start-Up Companies - Tedi Supriadi; Suryanto Suryanto (Indonesian Business Review, 2023)
This study is a literature review study that aims to see the role of job satisfaction on turnover intention, especially in start-up companies. Start-up companies today have the opportunity to grow rapidly supported by technology and information. Many interesting things can be reviewed from start-up companies, one of which is that start-up companies are dominated by Gen Z and millennials. Where generation Z and millennials are known for their characteristics or attitudes that easily feel bored when they can't get the opportunity to develop and easily feel bored with monotonous types of work. So that this triggers the emergence of turnover intention, including start-up companies. For this reason, it is necessary to make efforts to minimize the emergence of turnover intention through increasing and understanding what factors can increase job satisfaction so as to minimize the emergence of turnover intention from each individual in the start-up organization.